League Three Football Competition Management, Jambi Province - Izin, M Alpa; Sulaiman, Sulaiman; Nasuka, Nasuka (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
The background of this research is to know the management condition in the Three League Soccer Competition, Jambi Province. This study purposed to Analyze Human Resource Management in the League Three football competition Jambi Province, Analyze Funding Management in the League Three football competition, Analyze Management Methods in the League Three football competition in Jambi Province, Analyze the Management of Facilities and Infrastructure in the League Three Jambi Province football competition. Analyzed Technology Management in the League Three football Competition Jambi Province and Analyzed Marketing Management in the League Three Football Competition Jambi Province. This research method uses qualitative research methods. The research used a naturalistic interactive qualitative research approach, or a natural research. The results were human resource management is categorized as good and is under the planned process, financial management is categorized as moderate because there was no collaboration with sponsors and there was no contribution from the local government, the management method is categorized as good because in its implementation the competition was running well according to with the planned objectives, management of facilities and infrastructure can be categorized as good. Because in holding a competition, it already has adequate facilities, technology management is categorized as good because it already had technology help administrators carry out tasks in the office or in the field, marketing management is categorized as good, because in marketing In this competition, the management has collaborated with print media and other electronic media.